Synthesis and Properties of pH‐Dependent Gemini Surfactants Containing Multiple Carboxyl Groups. Issue 2 (14th January 2020) - Qiao, Longyin; Zhang, Wanjing; Xu, Libo; Han, Fu; Zhou, Yawen; Xu, Baocai
Abstract: A series of Gemini surfactants N, N″‐dialkyl‐N, N′, N″‐tripropionate diethylenetriamine (referred as DTPDT‐n, where n is the length of the hydrocarbon chain, n = 10, 12, 14) were synthesized, which have three carboxylic head‐groups and two hydrophobic alkane chains. The products were characterized by means of nuclear magnetic resonance and mass spectrometry. The physicochemical properties of DTPDT‐n surfactants with different hydrocarbon chain lengths were studied such as isoelectric point, surface activities, emulsifying properties, and foam properties. It is showed that these compounds exhibit pH‐dependent protonation‐deprotonation behavior. The isoelectric points of DTPDT‐n surfactants are between 3.40 and 10.90. The critical micellar concentration ( cmc ) of all three surfactants are lower than the corresponding monomeric surfactants (single head group, single‐chain), especially DTPDT‐14, whose cmc can reach 2.29 × 10 −5 mol/L. With an increase in the length of the alkyl chain, the solubility of the surfactants decreases and the surface tension of the three surfactants at cmc increases. In consideration of pH, all of three surfactants appear better emulsifying capacity and foaming property under weak alkaline conditions. DTPDT‐14 has the best performance of emulsifying capacity among the three surfactants. DTPDT‐10 has excellent foaming ability and foam stability.